Thromboxane A(2) contributes to the mediation of flow-induced responses of skeletal muscle venules: role of cyclooxygenases 1 and 2. - Racz, A; Veresh, Z; Erdei, N; Bagi, Z; Koller, A (2009)
BACKGROUND: It has been shown that increases in intraluminal flow elicit dilation in venules, but the mediation of response is not yet clarified. We hypothesized that - in addition to nitric oxide (NO) and dilator prostaglandins (PGI(2)/ PGE(2)) - thromboxane A(2) (TxA(2)) contributes to the mediation of flow-induced responses of venules. METHODS AND RESULTS: Isolated rat gracilis muscle venules (259 +/- 11 microm at 10 mm Hg) dilated as a function of intraluminal flow, which was augmented in the presence of the TxA(2) receptor antagonist SQ 29,548 or the TxA(2) synthase inhibitor ozagrel. In the presence of SQ 29,548, indomethacin or Nomega-nitro-L-arginine methyl-ester decreased flow-induced dilations, whereas in their simultaneous presence dilations were abolished. The selective cyclooxygenase (COX) 1 inhibitor SC 560 reduced, whereas the selective COX-2 inhibitor NS 398 enhanced flow-induced dilations. Immunohistochemistry showed that both COX-1 and COX-2 are present in the wall of venules. CONCLUSION: In skeletal muscle venules, increases in intraluminal flow elicit production of constrictor TxA(2), in addition to the dilator NO and PGI(2)/PGE(2), with an overall effect of limited dilation. These mediators are likely to have important roles in the multiple feedback regulation of wall shear stress in venules during changes in blood flow velocity and/or viscosity.